Deformation-induced martensite in 304 stainless steel during cavitation erosion: Effect on passive film stability and the interaction between cavitation erosion and corrosion. (March 2022) - Li, Z.X.; Zhang, L.M.; Udoh, I.I.; Ma, A.L.; Zheng, Y.G.
Abstract: The effect of deformation-induced martensite on the corrosion behavior and the interaction between cavitation erosion (CE) and corrosion of 304 stainless steel (SS) was investigated in this work. It was found that the content of deformation-induced martensite showed an increasing trend at the early CE stage, then a descent with the extension of CE time. A negative correlation between the pitting potential and the martensitic content was shown, indicating that the existence of martensite promoted the pitting sensitivity of 304 SS. Meanwhile, the corrosion current density and the carrier density gradually increased with the prolongation of CE time, implying the decreased stability of passive films. Results of the interaction between CE and corrosion demonstrated that the deformation-induced martensite mainly affected the pure CE mechanical damage, displaying an increased damage percentage with CE time. At the same time, the accelerating effect of corrosion to CE also had an important effect on the material damage, which should be attributed to the reduced resistance to pitting, accelerating the formation and propagation of cracks around corrosion pits. Highlights: Deformation-induced martensite promoted the pitting sensitivity of 304 SS. The existence of martensite reduced the stability of passive films. Deformation-induced martensite mainly affected the pure CE mechanical damage. Accelerating effect of corrosion to CE also played a key role on material damage. The corrosion pits accelerated the formation and propagation of CE cracks.